Integration of computational thinking into STEM activities: an example of an interdisciplinary unplugged programming activity. (3rd July 2022) - Özdinç, Fatih; Kaya, Gökhan; Mumcu, Filiz; Yıldız, Bahadır
ABSTRACT: STEM and computer science (CS) education are some of the most important research topics of the last decade. The idea that CS should be a part of STEM is becoming more and more common. The most important goals of integrating CS into STEM are to develop students' computational thinking (CT) and problem-solving skills. STEM education creates a natural context for integrating CT into learning and teaching processes. However, applied studies are needed since the subject is new and open to development. In this study, we designed an interdisciplinary unplugged programming activity to integrate CT into STEM activities which we then implemented in a professional development course (PD) with the participation of STEM teachers. To evaluate the effectiveness, an open-ended questionnaire was given to the teachers and the results were analyzed. Accordingly, the teachers stated that the activity was exemplary in applying the interdisciplinary approach and enabling the perspectives of different disciplines to be seen by other subject-area teachers. Also, using unplugged programming activities in teacher education provides an important example. Teachers who want to conduct unplugged programming activities in their classrooms, learn how to integrate CT into STEM, are interested in the practice to support their students' research skills, and aim to support students' 21st-century skills can also use this activity. The interdisciplinary structure of the activity and its example of integrating CT into STEM will guide practitioners and researchers in the field.